Development of Powerpoint-Based Interactive Media on Theme 8 Subtheme 1 in Elementary School - Nurkhodri, Muhammad; Dafit, Febrina (LPPM Undiksha, 2022)
The use of media in learning in elementary schools is an important part that must receive attention from educators. The use of interactive media is needed by elementary schools so that the learning provided becomes more effective and efficient. This study aims to develop interactive media based on powerpoint on the theme of 8 sub-theme 1 in class III of elementary school during offline learning activities. This research is a development research and uses the ADDIE model. The types of data taken from this development are qualitative data and quantitative data. The population of this research is third grade students. The trial conducted was a limited-scale trial with a sample of 6 students with different learning score categories. Data collection techniques consist of two types, namely the first teacher and student response questionnaire, second validation sheet material experts, media experts and linguists. Based on the results of research from media experts with a total of 93.33%, material experts with a total of 90.83% and linguists with a total of 90.94% and the overall results of 91.1% concluded that it is very valid to be used as a learning medium. The results of the analysis of teacher responses with a total of 94% and students with a total of 88.33% and the total results of 91.16% concluded that practical media were used in the learning process activities took place.